Association between reported sleep need and sleepiness at the wheel: comparative study on French highways between 1996 and 2011. Issue 12 (21st December 2016) - Quera-Salva, M A; Hartley, S; Sauvagnac-Quera, R; Sagaspe, P; Taillard, J; Contrand, B; Micoulaud, J A; Lagarde, E; Barbot, F; Philip, P
Abstract : Objective: To investigate the evolution over 15 years of sleep schedules, sleepiness at the wheel and driving risk among highway drivers. Methods: Comparative survey including questions on usual sleep schedules and before the trip, sleepiness at the wheel, the Epworth sleepiness scale, Basic Nordic Sleep Questionnaire (BNSQ) and a travel questionnaire. Results: 80% of drivers stopped by the highway patrol agreed to participate in both studies with a total of 3545 drivers in 2011 and 2196 drivers in 1996 interviewed. After standardisation based on sex, age and mean annual driving distance, drivers in 2011 reported shorter sleep time on week days (p<0.0001), and week-ends (p<0.0001) and shorter optimal sleep time (p<0.0001) compared to 1996 drivers. There were more drivers sleepy at the wheel in 2011 than in 1996 (p<0.0001) and 2.5 times more drivers in 2011 than in 1996 had an Epworth sleepiness score >15 indicating severe sleepiness. Conclusions: Even if drivers in 2011 reported good sleep hygiene prior to a highway journey, drivers have reduced their mean weekly sleep duration over 15 years and have a higher risk of sleepiness at the wheel. Sleep hygiene for automobile drivers remains an important concept to address.